2009
DOI: 10.1007/s11240-009-9571-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficiency of micropropagation from lateral buds and shoot tips of Rubus

Abstract: Factors affecting micropropagation efficiency of 32 selections of Rubus, including the pre-treatment and initiation culture stages, were investigated. Chilling at 4°C for 6 weeks as a pre-treatment significantly promoted in vitro initiation culture; up to 65% of initiation cultures post chilling were successful. The cytokinin 6-benzyladenine (BA) was the most effective of the three tested for promotion of multiple shoot development in culture, with an average of three to seven shoots or plantlets developed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
0
24
0
11
Order By: Relevance
“…The reason why micropropagation or in vitro plant regeneration from the culture of axillary buds has been reported to be paramount is that it is able to create clones which uphold the properties of the mother plant [17]. The most noteworthy element in acquiring a vast quantity of plantlets via micropropagation is using a suitable culture medium along with formulating the plant growth regulators like cytokinins with the aim of inducing and propagating the in vitro axillary buds [18]. Nevertheless, there is lack of surveys investigating the propagation of P. betle so far.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why micropropagation or in vitro plant regeneration from the culture of axillary buds has been reported to be paramount is that it is able to create clones which uphold the properties of the mother plant [17]. The most noteworthy element in acquiring a vast quantity of plantlets via micropropagation is using a suitable culture medium along with formulating the plant growth regulators like cytokinins with the aim of inducing and propagating the in vitro axillary buds [18]. Nevertheless, there is lack of surveys investigating the propagation of P. betle so far.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha observado que varios cultivares de frambuesa responden a concentraciones que van desde 0.5 hasta 2 mg L -1 de BA en combinación con AIB o ANA, o solo zeatina (Graham et al, 1997;Palonem y Buszard, 1998;Debnath, 2004;Zawadzkay Orlikowska, 2006;Wu et al, 2009), o bien de 1 a 2 mg L -1 de tidiazuron con 0.5-1 mg L -1 de ácido 1H-indole-3-butanoico (AIB) (Swartz et al, 1990;Cousineau y Donnelly, 1991). The number of raspberry shoots produced in vitro depend largely on the concentration of cytokinins, specifically benzyladenine and on the propagated cultivar (Avitia and Rodriguez, 1984;McNicol and Graham, 1990).…”
Section: Resultados Y Discusión Formación De Brotesunclassified
“…The number of raspberry shoots produced in vitro depend largely on the concentration of cytokinins, specifically benzyladenine and on the propagated cultivar (Avitia and Rodriguez, 1984;McNicol and Graham, 1990). It has been observed that several cultivars of raspberry respond to concentrations ranging from 0.5 to 2 mg L -1 of BA in combination with IBA or IAA, or only zeatin (Graham et al, 1997;Palonem and Buszard, 1998;Debnath, 2004;Zawadzkay Orlikowska, 2006;Wu et al, 2009), or 1-2 mg L -1 of thidiazuron with 0.5-1 mg L -1 1H-indole-3-butanoic acid (IBA) (Swartz et al, 1990;Cousineau and Donnelly, 1991).…”
Section: Resultados Y Discusión Formación De Brotesmentioning
confidence: 99%
“…Resultados que coinciden con los obtenidos en el presente estudio, ya que la concentración 4,88 mM de nitrógeno (1/2 de sales), que mantiene la misma relación NO 3 /NH 4 que MS completo, produjo el mayor número y longitud de raíces. Ma et al (1996) y Wu et al (2009) también reportan resultados que concuerdan con los obtenidos en el presente estudio en la fase de enraizamiento.…”
Section: Figura 2 Plantas Enraizadas In Vitrounclassified
“…Alev y Arslan (2006) obtuvieron la mayor frecuencia de enraizamiento con un 50 % de explantes de rosa enraizados, en un medio que contenía la mitad de las sales de MS. Además, según Ramírez y Angarita (1990) se obtuvo un 100 % de enraizamiento in vitro de plantas de mora, con los macroelementos diluidos a la quinta parte; por lo que recomienda la dilución de los macroelementos en el medio de cultivo para mejorar los porcentajes de supervivencia y enraizamiento. Estos resultados se relacionan con los obtenidos por Wu et al (2009) que indican que una reducción de sales de un medio a un quinto, mejoran el enraizamiento de algunas especies del género Rubus hasta llegar a un 85 % de plantas enraizadas. Luna et al (2004), recomiendan el medio MS diluido 4 veces, para el enraizamiento in vitro de Ilex dumosa.…”
Section: Porcentaje De Plantas Enraizadasunclassified